Conspiracy involving Dilma’s government and her impeachment according to PSDB’s speech: regime of power and truth - Barros, Maria Irenilce Rodrigues (2020)
Within the French Discourse Analysis (AD) and Michel Foucault’s approach to the concepts of truth and power, this paper analyzed Aécio Neves’s inauguration speech when he was reelected as president of the Brazilian Social Democratic Party (PSDB), which took place in the 12th PSDB National Convention on July 5, 2015. The archeological, genealogical method in this study contributed to the description and interpretation of the speech. This corpus is relevant to understand the pathway built to Dilma Rousseff’s impeachment because it materialized linguistic components that were disseminated by the hegemonic media, the justice, and social and technological players. Statements like ‘fiscal pedaling, crisis, corruption’, etc. served this purpose. Communication vehicles started to explore these elements daily and transform them into media sensationalism against Dilma and the Labor’s Party (PT). Such statements were mentioned by ideological and political opponents of PT in the form of discursive and non-discursive practices, since these terms marked and/or demarcated the Brazilian population’s daily lives, mainly inducing protests against the government on the streets or on social media. The keynote of Aécio’s speech includes two opposing topics: he praised PSDB’s management and negatively assessed Dilma’s administration to defame and depreciate her. The analysis showed that Aécio gathered information to provoke Dilma’s dismissal to replace her government for an ideologically different one. The term ‘democracy’ appears contradictorily in the speech: on one hand, Aécio reaffirms he fights for democracy, that is why he defends it; on the other hand, he actually uses it to later (corrupt)disrupt it.